A new species of Troglopedetes Joseph, 1872 with eyes (Collembola, Paronellidae) from a Christmas Island Cave, Australia - Cipola, Nikolas Gioia; Greenslade, Penelope (Zootaxa, 2023)
A new species of Troglopedetes Joseph from a Christmas Island Cave, Australia is described and illustrated here. Troglopedetes eberhardi sp. nov. resembles other species by presence of eyes and dorsal chaetotaxy of the second thoracic segment to third abdominal segment, but differs in head chaetotaxy, fourth abdominal segment and elongated unguis median tooth, which character is documented here in the genus for the first time. A comparison and identification key for all eyed species is provided. This is the first record of Troglopedetes for Australia and the genus now has 37 nominal species, of which nine have eyes.